Assessing the Efficacy of a Self-Developed Guide for Repair and Maintenance of Selected Domestic Electrical Appliances by Technical College Students in Akwa Ibom State - Gangkwi, J. H.; Kanu, M. C.; Mamuda, T. (Journal of Research in Industrial Technology and Educational Studies, 2026)
This study assessed the efficacy of a self-developed guide for repair and maintenance of selected domestic electrical appliances by Technical College students in Akwa Ibom state. Three specific purposes, three research questions and one null hypothesis were postulated to guide the conduct of the study. The non-randomized pre-test, post-test quasi-experimental design was adopted for the study. The population consisted of all 1,724 TC II students in Government Technical College Ewet, Uyo Local Government Area, 19 Technical College teachers with major in electrical /electronics and all the eight lecturers in Industrial Technology Education Department in University of Uyo. A 29 item researcher-developed instrument titled “Self-Help Guide for Repair and Maintenance of Domestic Electrical Appliances Questionnaire”, Practical instructional tasks and practical checklist developed by the researcher were used to elicit data for the study. The instruments were validated by three experts, two from Industrial Technology Education Department, University of Uyo and one from Government Technical College Ewet, Uyo. A reliability index of 0.88 was obtained using the Cronbach’s Alpha procedure. The instrument were administered and data collected in-situ. The data obtained were analysed using mean values to answer the research questions while Analysis of Covariance (ANCOVA) was used to test the null hypothesis at 0.05 level of significance. The findings of the study revealed 15 safety precautions and 14 tools for carrying out repair and maintenance of domestic electrical appliances. The study also revealed a significant difference in performance among students who used and those who did not use the self-help guide for practical repair and maintenance during the experiment. It was recommended that the self-help guide be adopted for teaching and learning practical skills in technical colleges and vocational institutions. Also, that workshops and seminars should be organized by the National Directorate of Employment and related government agencies to enlighten electrical repair and maintenance trainers and other vocational and technical teachers in order to improve their knowledge and skills on the use of self-help guide for repair and maintenance of domestic electrical appliances.